The Law of Internal Security in Mexico: between the reason of State and the justification of human rights - Medellín Mendoza, Laura Nelly (FLACSO - Sede Ecuador, 2018)
We present an exploratory qualitative analysis from the standpoint of Political Science about the argumentation sustained in the initiatives of the Internal Security Law (LSI) presented by the Institutional Revolutionary Party, the National Action Party and the Party of the Democratic Revolution. Two operative concepts guide the analysis: reason of State and human rights, both present in the implicit justifications of those who promote the law, and in those of its detractors, who qualify it as a violation of human rights. In this last point, we concentrate on reviewing two unconstitutionality actions presented by the National Commission of Human Rights and by a group of opposition legislators who did not vote in favor of the LSI in the Sixty-Third Legislature. We aim to show the collision of arguments between the vision of the State, which wants to legally legitimize the presence of the Army in the streets, and the other vision, which assumes a guaranteeing justification of human rights.